M115. COGNITIVE FUNCTION IN BIPOLAR AND SCHIZOPHRENIA OFFSPRING: FINDINGS ACROSS THE NEURODEVELOPMENTAL CONTINUUM. (18th May 2020) - Valli, Isabel; De la Serna, Elena; Borras, Roger; Daniel, Ilzarbe; Baeza, Inmaculada; Dolores Picouto, Maria; Rubio, Patricia; Baltasar, Itziar; Moreno, Dolores; Castro-Fornieles, Josefina; Sugranyes, Gisela
Abstract: Background: Neurocognitive impairment is considered to lie on a continuum of severity across schizophrenia (SZ) and bipolar disorder (BP), possibly reflecting a continuum of neurodevelopmental load. Due to the known heterogeneity, performance patterns across both disorders have been examined using clustering approaches, which previously identified subgroups with different levels of impairment, from none to widespread and severe. We, for the first time, used this approach to examine cognitive function in children and youth at familial risk of developing SZ and BP, in order to investigate cognitive profiles earlier on in the neurodevelopmental pathway. Methods: 220 participants, 49 offspring of individuals with schizophrenia (SZO), 90 offspring of individuals with bipolar disorder (BPO) and 81 healthy controls (HC), underwent a comprehensive cognitive assessment. Measures of attention, verbal memory, visual memory, executive function, working memory, and processing speed were used to group high-risk offspring. The k-means clustering with elbow method was used to determine the optimal number of clusters. High-risk offspring were then each assigned to a specific cluster. Cognitive performance within each of the clusters was compared to that of HC in order to describe the distribution of impairments across different cognitive domains and their severity. Between–cluster comparisons were then performed in terms of clinical and functioning variables. Results: Three cognitive subgroups were identified for high-risk offspring: a global impairment group (19.5%) with severe impairments across most cognitive domains, a selective impairment group (46%) with moderate deficits across specific domains, and a cognitively intact group (34.5%) with performance comparable to that of healthy controls. Both SZO and BPO were represented in each of the three clusters. However a larger proportion of the SZO (30.6%) than of the BPO (13.3%) were characterised by widespread cognitive dysfunction, whereas BPO (41.1%) were more frequently cognitively spared relative to SZO (22.4%). Individuals in the global cognitive impairment group displayed significantly poorer clinical and functioning measures relative to the other two clusters. Discussion: Three cognitive subgroups were identified in BP and SZ offspring, a global impairment group, a selective impairment group and a cognitively intact group. The clustering pattern identified overlaps with that previously observed after illness onset. Findings are in line with the known heterogeneity in cognitive impairment across SZ and BP and can contribute to elucidate the timeframe of its emergence. Using cognitive function as a proxy measure of neurodevelopmental load, the findings point to a gradient in individuals at genetic risk of SZ and BP. They have therefore important implications for the understanding of potentially different neurodevelopmental trajectories within SZ and BP, hence for patient stratification in research and clinical practice.